Muscle energetics and the cardiovascular response to isometric exercise and post-exercise circulatory occlusion following exercise-induced muscle damage: insights from multiparametric MRI - Zambolin, Fabio; Lagacé, Jean-Christophe; Pinner, Susan; McStravick, James; Smith, Fiona E.; Kennerley, Aneurin J.; McPhee, Jamie S. (Frontiers in Physiology, 2025)
IntroductionSkeletal muscles damaged by exercise exhibit disturbed energy metabolism and microvascular function for several days. However, it remains unclear whether these local changes might affect systemic cardiovascular responses to exercise. The present study aimed to investigate whether damaged muscles show changes in energy metabolism and oxygenation that influence systemic cardiovascular responses to exercise and post-exercise circulatory occlusion (PECO).MethodsA novel multi-parametric magnetic resonance imaging and spectroscopy approach was applied. Twelve healthy male participants completed assessments before and 48 h after 40 min of downhill running (20% decline). The assessments included muscle function, inflammation, and multi-parametric imaging at rest, exercise, and post-exercise occlusion using 31P spectroscopy, 1H- and muscle blood oxygen level-dependent imaging, and 23Na+ imaging to assess phosphate metabolism, oxygenation, and sodium disturbances. The mean arterial pressure (MAP) and heart rate (HR) were recorded throughout the MRI sequences.ResultsForty-eight hours after downhill running, muscle inflammation and Na+ disturbances were evident (both p < 0.05). Muscle oxygenation was lower and inorganic phosphates were higher during exercise and PECO than at baseline (both p < 0.05). However, MAP and HR during exercise and PECO remained unchanged at 48 h compared with baseline.ConclusionOur multi-parametric MRI approach provides new insights into the local effects of muscle damage on energy metabolism, oxygenation, and Na+. Despite these local metabolic and microvascular disturbances, systemic cardiovascular responses, as indicated by MAP and HR, remained unchanged. These new findings suggest a dissociation between muscle metabolites, oxygenation, and the cardiovascular response to exercise and PECO 48 h after damaging exercise.